202k views
1 vote
Please help.

The graph shows a cubic function:

1. How many real roots does the function have?
A. 0
B. 1
C. 2
D. 4
E. 3

2. Complete the equation of the graphed function. y= (x - ?)(x + ?)^2
The choices are 0,3,1,2,4

Please help. The graph shows a cubic function: 1. How many real roots does the function-example-1
User Lukmdo
by
5.3k points

2 Answers

5 votes

Answer:

We are to solve the cube root equation, ∛x – 1 + 2 = 0

Solve like terms; subtract 1 from 2 to get -1 (-1 + 2 = +1)

Therefore, ∛x + 1 = 0

Move +1 to the right side of the equation, since it does not contain the variable to solve for.

∛x + 1 = 0

Subtract 1 from both sides of the equation

∛x + 1 – 1 = 0 – 1

∛x = -1

Cube both sides of the equation in order to remove the radical on the left side

(∛x)^3 = (-1)^3

x = -1We are to solve the cube root equation, ∛x – 1 + 2 = 0

Solve like terms; subtract 1 from 2 to get -1 (-1 + 2 = +1)

Therefore, ∛x + 1 = 0

Move +1 to the right side of the equation, since it does not contain the variable to solve for.

∛x + 1 = 0

Subtract 1 from both sides of the equation

∛x + 1 – 1 = 0 – 1

∛x = -1

Cube both sides of the equation in order to remove the radical on the left side

(∛x)^3 = (-1)^3

x = -1We are to solve the cube root equation, ∛x – 1 + 2 = 0

Solve like terms; subtract 1 from 2 to get -1 (-1 + 2 = +1)

Therefore, ∛x + 1 = 0

Move +1 to the right side of the equation, since it does not contain the variable to solve for.

∛x + 1 = 0

Subtract 1 from both sides of the equation

∛x + 1 – 1 = 0 – 1

∛x = -1

Cube both sides of the equation in order to remove the radical on the left side

(∛x)^3 = (-1)^3

x = -1We are to solve the cube root equation, ∛x – 1 + 2 = 0

Solve like terms; subtract 1 from 2 to get -1 (-1 + 2 = +1)

Therefore, ∛x + 1 = 0

Move +1 to the right side of the equation, since it does not contain the variable to solve for.

∛x + 1 = 0

Subtract 1 from both sides of the equation

∛x + 1 – 1 = 0 – 1

∛x = -1

Cube both sides of the equation in order to remove the radical on the left side

(∛x)^3 = (-1)^3

x = -1We are to solve the cube root equation, ∛x – 1 + 2 = 0

Solve like terms; subtract 1 from 2 to get -1 (-1 + 2 = +1)

Therefore, ∛x + 1 = 0

Move +1 to the right side of the equation, since it does not contain the variable to solve for.

∛x + 1 = 0

Subtract 1 from both sides of the equation

∛x + 1 – 1 = 0 – 1

∛x = -1

Cube both sides of the equation in order to remove the radical on the left side

(∛x)^3 = (-1)^3

x = -1

Explanation:

User Kennon
by
5.3k points
3 votes

The polynomial has three real roots (of which one counts twice). It's formula is
y= (x - 1)(x + 2)^2


The roots of a polynomial are the points in which the polynomial inersects the x-axis. So, you might be tempted to say that there are two roots,
x=-2 and
x = 1.


But now let's face the problem in an analytic way: if
x_0 is a solution for the polynomial
p(x), then
p(x) can be factored as
(x-x_0)r(x) where
r(x) is some remainder.


So, since we are sure that
x=-2 and
x = 1 are solutions, we know that we can write our polynomial as



p(x) = (x-1)(x+2)r(x)


But since the polynomial is a cubic (i.e. degree 3),
r(x) must be a polynomial of degree 1, i.e.
r(x)=x-k for some
k \in \mathbb{R}


But then we would have



p(x) = (x-1)(x+2)(x-k)


and so we would have a third solution
x=k, but we can see from the graph that the only solutions are
x=-2 and
x = 1.


This means that
r(x) is actually a copy of one of the two other factors, so that it doesn't add new solutions. So, we have two cases:



r(x) = x-1 \implies p(x) = (x-1)^2(x+2)


or



r(x) = x+2 \implies p(x) = (x-1)(x+2)^2


The answer lies in the shape of the polynomial: you can see that the graph is tangent to the x-axis in
x=-2, whereas it crosses the x-axis at
x=1. This tells us that the double solution is
x=-2, and thus the correct solution is
p(x) = (x-1)(x+2)^2

User Floam
by
4.9k points